A NEW TRIAL TO SEARCH FOR ISOTOPICALLY ANOMALOUS OSMIUM AND RUTHENIUM IN FINE-GRAINED CA, AL-RICH ALLENDE INCLUSIONS BY RADIOCHEMICAL NEUTRON ACTIVATION ANALYSIS - Yongzhong L.; Chifang C. (My University, 1997)
The ratios of 184Os190Os and 96Ru102Ru in five fine-grained Ca, Al-rich Allende inclusions (CAIs) were determined simultaneously and precisely by radiochemical neutron activation analysis (RNAA). The results show that their deviations relative to the terrestrial chemical reagent are within -1.5% and 1.9% for 184Os190Os and 96Ru102Ru, respectively. It seems unlikely that the isotopic anomalies of Os and Ru exist at a magnitude of more than +/-2% in bulk fine-grained Allende CAIs. Whereas the possibility that the fine-grained Allende CAIs measured in this work do not contain presolar components and thus have normal isotopic compositions cannot be excluded, we believe that our data may most plausibly be interpreted as the anomalies carried by submicron-size metal alloys thought to be the presolar grains were homogenized during the processes of sample digestion and chemical separation. Os and Ru concentrations in five fine-grained CAIs were determined by comparison with the activities of the known amounts of Os and Ru standards, respectively. In contrast to the coarse-grained Allende CAIs, Os and Ru were greatly depleted in these five fine-grained CAIs. The mean enrichment factors of Os and Ru relative to C1 chondrite were 2.82 and 2.99, respectively. In addition, Os is depleted relative to Ru in four of five fine-grained Allende CAIs, and a large fractionation between Os and Ru is observed. The C1 chondrite-normalized Os/Ru enrichment factor ranges from 0.23 to 2.50 in five fine-grained Allende CAIs. These results support the non-equilibrium incomplete condensation model for the origin of fine-grained Allende CAIs. It suggests that the fine-grained Allende CAIs probably contain much less hcp alloy grains, and thus the primordial signatures of isotope and Os/Ru ratio might more readily survive the equilibrium process than those in coarse-grained Allende CAIs. Consequently, it is undeniable that the fine-grained Allende CAI is one of the most promising hunting grounds to search for isotopically anomalous Os and Ru.
Keywords: ALLENDE INCLUSION; OSMIUM; RUTHENIUM; ISOTOPIC ANOMALY; RADIOCHEMICAL NEUTRON ACTIVATION ANALYSIS